PENGARUH LATIHAN SQUAT JUMP TERHADAP POWER OTOT TUNGKAI PADA SISWI SMA NEGERI 1 BENAI YANG MENGIKUTI EKSTRAKURIKULER ATLETIK LOMPAT JAUH - Era Marliza; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is done to find wheter there is the effect of squat jumptraining toward leg muscle power on female student at SMA Negeri 1 Benai who is following extracurricular of long jump. There is a shortage on power of the leg that is done by student when doing long jumps. This is caused the leg muscle power on female student SMA Negeri 1 still lacking. The form of this research is using experiments. With an extracurricular female student population of SMA Negeri 1 Benai, Totaling 20 people. The instrument used in this research was to use a Standing Board Jump that aims to measure leg muscle power. Afterward the data is processed with statistics to test normality and liliefors test at a significance level43 of 0,05. The hypothesis proposed is the effect of Squat Jump training on leg muscle power in long jump athletic extracurricular activities. Based on the analysis of the t test produces a Tcount of 12.20 and 1.792 Ttable which means Tcount > Ttable. Based on statistical data analysis, there is an average Pree Test of 3,223 and an average Post Test of 3,306, Then the datais normal. Thus, it can be concluded that there is an effect of squat jump training on leg muscle power in the extracurricular athletics of long jump at SMA Negeri 1 Benai.Key Word: Squat Jump, Leg Muscle Power